2015
DOI: 10.1002/adhm.201400763
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cellular Response Pattern to Phosphorus Ion is a New Target for the Design of Tissue‐Engineered Blood Vessel

Abstract: Regulation of cellular response pattern to phosphorus ion (PI) is a new target for the design of tissue-engineered materials. Changing cellular response pattern to high PI can maintain monocyte/macrophage survival in TEBV and the signal of increasing PI can be converted by klotho to the adenosine signals through the regulation of energy metabolism in monocytes/macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Therefore, it is of great significance to the long‐term patency of TEBV through the target delivery of microenvironment optimizing molecules to EPCs while specifically capturing EPCs. Currently, the characterization method of one molecule with multiple functions is widely adopted, yet it still has a lot of deficiencies including limited effect and different concentration of molecules required for different functions . Based on exosomes and PEI/AuNP, one TEBV enabling the capturing of EPCs and the optimization of microenvironment was constructed through the self‐assembly mode.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is of great significance to the long‐term patency of TEBV through the target delivery of microenvironment optimizing molecules to EPCs while specifically capturing EPCs. Currently, the characterization method of one molecule with multiple functions is widely adopted, yet it still has a lot of deficiencies including limited effect and different concentration of molecules required for different functions . Based on exosomes and PEI/AuNP, one TEBV enabling the capturing of EPCs and the optimization of microenvironment was constructed through the self‐assembly mode.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, as a vesicular structure, exosomes did not produce any side effect resulted from the transplantation of MSCs, such as the differentiation of terminal cells. Klotho is an antiaging protein, which can inhibit the apoptosis, and the latest study reveals that klotho can capture the circulating EPCs . As the increase of klotho protein on the surface of exosome was induced by enhancing the expression of klotho protein in donor cells, the purpose of early endothelialization of TEBV could be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After TEBV transplantation, released extracellular nucleotides (ATP and ADP) will trigger inflammation and lead to an inflammatory microenvironment. Apyrase and 5′-NT hydrolyze these extracellular nucleotides into adenosine, thus altering an ATP/ADP-driven pro-inflammatory milieu to an adenosine-induced anti-inflammatory environment and accelerating the endothelialization of TEBVs. , Both in vitro and in vivo experiments have shown that the RGO-enzyme-coated TEBVs had good antiplatelet and antithrombotic functions. We believe that these easily prepared vessels can provide options for the preparation of clinically available TEBVs.…”
mentioning
confidence: 99%
“…Estudos in vitro demonstraram que a sobrecarga de P causa apoptose de células ósseas e endoteliais de maneira tempo e dose dependente (Meleti et al, 2000;Chen et al, 2015). Mansfield e cols.…”
Section: Fisiologia Do Intestino Delgadounclassified